Pengaruh Alih Baring Dan Minyak Kelapa (VCO) Terhadap Dekubitus Pada Pasien Bedrest Dengan Stroke Non Hemoragik (SNH) Di Rumah Sakit Pusat Otak Nasional Jakarta Timur : The Effect of Bed Rest and Coconut Oil (VCO) on Pressure Ulcers in Bedrest Patients with Non-Hemorrhagic Stroke (SNH) at the National Brain Center Hospital, East Jakarta - DELIMA, DIAR (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: The impact of stroke can cause decubitus. Decubitus not only affects the patient's quality of life, but can also cause life-threatening sepsis. The purpose of this study was to determine the effect of bed transfer and coconut oil (VCO) on decubitus in bedrest patients with non-hemorrhagic stroke (SNH) pre-treatment at the National Brain Center Hospital, East Jakarta. Methods: The research design that will be used in this study is Pre-Experimental Designs. This research design conducts pretest and posttest but without a control group. The population in this study were non-hemorrhagic stroke (SNH) patients with an average of 200 patients per month. The sample that has been studied was 15 people. The sampling technique used in this study used the purposive sampling technique. Bivariate analysis was used using the Marginal Homogeneity Test method. The Marginal Homogeneity Test is a nonparametric statistical test. Results: Based on the results of the study, it is known that before the intervention of bed rest and coconut oil (VCO) based on the study, the healing of decubitus in the pretest was good and after the intervention remained good, namely 4 people (100%); the healing of decubitus in the pretest was sufficient and after the intervention became good, namely 14 people (100%) and the healing of decubitus in the pretest was lacking and after the intervention remained lacking namely 1 person (50%). The results of the statistical test showed that the p-value was 0,003 meaning P < 0,05 Discussion: There is an effect of bed rest and coconut oil (VCO) on decubitus in bedrest patients with non-hemorrhagic stroke (SNH) at the National Brain Center Hospital, East Jakarta in 2024. Suggestions for patients to be able to apply bed rest and coconut oil (VCO) for the healing of decubitus.